Effects of physiotherapy associated to virtual games in pain perception and heart rate variability in cases of low back pain - Zavarize, Sergio Fernando; Paschoal, Mário Augusto; Wechsler, Solange Muglia (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The virtual games when appropriately used can stimulate brain activity and excite the creative energy. Therefore, it is important to assess the implications of their use in pain perception in individuals with low back pain (LBP), a disease that affects about 80% of the world’s population. Objective: was to evaluate the effects of virtual games combined with a physiotherapy program on the pain perception and Heart Rate Variability (HRV) in people with LBP. Method: the participants were 21 adults with clinical diagnosis of LBP, aged 24-61 years, of both sexes, divided into two groups. Five weekly meetings were provided. Group 1 participated in a physical therapy program and group 2 participated in the same physical therapy program plus joint sessions with virtual games. The instruments used were a heart rate monitor; a tablet for games; a shortwave equipment; visual analogue scale (VAS); and McGill’s Pain Questionnaire. The measurements were performed before and after the program. Results: Reduction in pain was observed in both groups, being higher in group 2, the one that used the games. Conclusion: There was a decrease in parasympathetic activity in group 2, which indicates that the distraction factor promoted by the games influenced the pain perception.